Influence of Water-Miscible Ionic Liquid 1-Butyl-3- methylimidazolium Tetrafluoroborate [BMIM][BF4] on Acetylcholinesterase Inhibition-Based Spectrometric Assay for Parathion Methyl - CHEN, JIN; MIAO, JIGEN; QI, XIAOXUE; MIAO, YUQING (Asian Journal of Chemistry, 2010)
The influences of water-miscible ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([BMIM][BF4]) on acetylcholinesterase (AChE) inhibition-based organophosphorous assay were investigated. On the one hand, water-miscible [BMIM][BF4] competitively removes the essential hydration shell from the AChE molecule and thus enzyme activity is inhibited slightly. On the other hand, the existence of [BMIM][BF4] improves the inhibition binding between AChE and para-thion methyl. 5.1 % [BMIM][BF4] leds to the best inhibition rate. Ionic liquids mixed aqueous solutions show the potential to provide a promising and effective medium in organophosphorous assay with AChE.